EFFICIENCY COMPARISON OF PATHFINDING ALGORITHMS A* AND DIJKSTRA’S IN TWO DIMENSIONAL GRID - Česlis, Intars; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
The shortest path finding algorithms are applied more and more in different industries. There are many pathfinding algorithms, but the most of them differ from their modified versions. The goal of this work was to create A* and Dijkstra’s pathfinding algorithms and compare their execution time.